Chronic hepatitis C: treat or wait? A prospective study on reasons for treatment or nontreatment in the era of first-generation protease inhibitors. Issue 2 (February 2016) - Feillant, Marie; Jézéquel, Caroline; Lison, Hortensia; Delluc, Aurélien; Tanné, Florence; Le Gruyer, Antonia; Ben Ali, Zeineb; Renard, Isabelle; Latournerie, Marianne; Deugnier, Yves; Garioud, Armand; Cadranel, Jean-François; et al.
Abstract : Background and aims: In many countries, current treatment for patients with chronic hepatitis C involves a combination of peginterferon and ribavirin, associated with a protease inhibitor for hepatitis C virus genotype 1. More recent and efficient less toxic antiviral treatments are now available for some patients. Thus, the decision to treat or to wait is challenging. The aims of this study were to: (a) estimate the proportion of treated patients, (b) evaluate the reasons for this decision, and (c) examine the patients' points-of-view in treatment decision. Methods: This was a prospective study conducted at three French referral centers between March and June 2013. Epidemiological and virological data, reasons for treatment or nontreatment, and data on the doctors' and patients' choices were collected. Results: A total of 255 patients were analyzed. Only 52.6% of patients with fibrosis of 2 or higher were treated. Treatment uptake was reduced in the following groups: previously treated patients, those with poor tolerance during prior treatment, those with heavy alcohol consumption, and those with hepatocellular carcinoma. Of the cirrhotic patients, 55% were not treated: 51.1% had a contraindication, 22.2% had a previous nonresponse. When treatment was refused by the patient, fear of side effects and professional problems were the most frequently cited reasons (90 and 40%, respectively). Conclusion: Patients were treated primarily according to consensus guidelines. However, only 45% of cirrhotic patients were treated. In 7.6% of the cases, the patient refused therapy. This study enabled us to measure the importance of patient choice in medical decision-making. Well-informed patients expected not only more efficient but also well-tolerated therapy.